2018
DOI: 10.1101/464685
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Checkpoint adaptation in repair-deficient cells drives aneuploidy and resistance to genotoxic agents

Abstract: Human cancers frequently harbour mutations in DNA repair genes, rendering the use of DNA damaging agents as an effective therapeutic intervention. As therapy-resistant cells often arise, it is important to better understand the molecular pathways that drive resistance in order to facilitate the eventual targeting of such processes. We employ repair-defective diploid yeast as a model to demonstrate that, in response to genotoxic challenges, nearly all cells eventually undergo checkpoint adaptation, resulting in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 85 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…It was initially shown that adaptation is important for survival of irradiated diploid cells when HR is compromised, while at the same time promoting genomic instability in the surviving progeny (Galgoczy and Toczyski 2001). This is supported by a recent study showing that adaptation to genotoxic challenge of HR-deficient diploid cells leads to aneuploid progeny that develops some form of resistance to a second genotoxic challenge (Bender et al 2018). To follow on a similar idea, in another setting, adaptation is required to survive telomere uncapping by loss of Cdc13 in established telomerase-independent survivors (Mersaoui et al 2015).…”
Section: Cell Survival and Genome Instability: Adaptation As A Doublementioning
confidence: 92%
“…It was initially shown that adaptation is important for survival of irradiated diploid cells when HR is compromised, while at the same time promoting genomic instability in the surviving progeny (Galgoczy and Toczyski 2001). This is supported by a recent study showing that adaptation to genotoxic challenge of HR-deficient diploid cells leads to aneuploid progeny that develops some form of resistance to a second genotoxic challenge (Bender et al 2018). To follow on a similar idea, in another setting, adaptation is required to survive telomere uncapping by loss of Cdc13 in established telomerase-independent survivors (Mersaoui et al 2015).…”
Section: Cell Survival and Genome Instability: Adaptation As A Doublementioning
confidence: 92%
“…This surveillance mechanism provides time to repair the damage, and only when repair has been successful, the checkpoint is extinguished and cells re-enter into the cell cycle [1,10,12,46,77,82,83]. In unicellular organisms, if DNA repair is not possible, cells can overcome DNA Damage through checkpoint adaptation [15,21,71,77,84]. Interestingly, mounting evidence indicates that this concept is not only found in unicellular eukaryotes like yeast but it might be extended also in multicellular organisms [10,16,76,77,85].…”
Section: Consequences Of Checkpoint Adaptationmentioning
confidence: 99%
“…For instance most cells that undergo checkpoint adaptation die, whereas some cells survive; surviving cells face two different fates: Some cells will die in subsequent phases of the cell cycle, but a small number of cells will survive and divide with damaged DNA [References [85,86,87] and references there in]. In line with this model, it has been demonstrated that in repair-defective diploid yeast, nearly all cells undergo checkpoint adaptation, resulting in the generation of aneuploid cells with whole chromosome losses that have acquired resistance to the initial genotoxic challenge [84]. An important consequence of this finding was the demonstration that adaptation inhibition, either pharmacologically or genetically, drastically reduces the occurrence of resistant cells [87,88,89].…”
Section: Consequences Of Checkpoint Adaptationmentioning
confidence: 99%
See 1 more Smart Citation